Development and validation of RP HPLC method for the estimation of Sofosbuvir and related impurity in bulk and pharmaceutical dosage form - Shiny Ganji; Satyavati Dhulipala; Appala Raju Nemala (SpringerOpen, 2021)
Abstract Background The present work is aimed at development and validation of RP HPLC method which is simple, specific, precise, and accurate for estimation of Sofosbuvir and its process-related impurity in bulk and pharmaceutical dosage forms. Extensive literature survey revealed no method for estimation of the above said. The chromatographic separation was achieved on Agilent Eclipse XDB-C18, 4.6 × 250 mm, 5 μm with mobile phase composed of 0.1% trifluoroacetic acid in 1000 ml of water:acetonitrile (50:50) using an isocratic mode of elution. Detection was made using UV detector at 260.0 nm and LC solution software for analysis of data. The developed method was validated according to ICH guidelines. Results The linearity of calibration curve for Sofosbuvir in concentration range of 160-480 μg/ml was good. The curve was linear for its process related impurity (Phosphoryl) in concentration range of 10-30 μg/ml. There exists a good correlation between peak area and analyte concentration. Retention time for Sofosbuvir was found to be 3.674 min and its impurity was 5.704 min. Relative standard deviation values for Sofosbuvir is 1.741 and its process related impurity is 0.043. LOD for Sofosbuvir and its impurity was found to be 0.01% (0.04 μg) and 0.03% (0.12 μg) respectively. LOQ for Sofosbuvir and its impurity was found to be 0.50% (0.125 μg) and 1.50% (0.375 μg) respectively. Conclusion All the results reveal that the proposed method was found to be highly sensitive, simple, precise, accurate, robust, and fast. Large number of samples can be analyzed in shorter time due to shorter retention times, so it can be successfully applied for routine analysis of Sofosbuvir and related phosphoryl impurity in bulk and pharmaceutical dosage forms.